Madrasah Leadership in the Post COVID-19 Era: Lesson Learn From Crisis in Indonesia - Maya NS; Arif Rahman; Sayid Habiburrahman (PT ARRUS Intelektual Indonesia, 2022)
This study wants to highlight how madrasah leadership is conceptualized and how madrasah leadership shifts after Covid-19. The pandemic crisis that occurred in Indonesia put pressure on so broad, including madrasah education. The challenges of madrasah leadership have entered a new phase after the Covid-19 outbreak began to subside, schools began to open together with other tasks that became the concern of madrasah leaders. This study uses a literature study approach, the data is obtained through the theoretical literature related to the topic of this research, the data is then analyzed descriptively. The results of this study indicate that the concept of madrasah leadership after Covid-19 experienced a drastic shift to a dynamic direction after facing various changing challenges. In addition, in the development of the shift in madrasah leadership after the Covid-19 period, it is necessary to consider further the following three styles of madrasah leadership being developed, namely: collaborative leadership, flexible-adaptive, and social justice. Abstrak Studi ini ingin menyoroti bagaimana kepemimpinan madrasah dikonseptualisasikan dan untuk bagaimana pergeseran kepemimpinan madrasah setelah Covid-19. Krisis pandemi yang terjadi di Indonesia memberikan tekanan yang begitu luas termasuk pendidikan madrasah. Tantangan kepemimpinan madrasah telah memasuki babak baru setelah wabah Covid-19 mulai mereda, sekolah mulai dibuka berbarengan dengan tugas lainnya yang menjadi perhatian pimpinan madrasah. Studi ini menggunakan pendekatan studi literatur, data diperoleh melalui literatur teoritis yang berkaitan dengan topik penelitian ini, data selanjutnya dilakukan analisis secara diskriptif. Hasil penelitian ini menunjukkan bahwa konsepsi kepemimpinan madrasah setelah Covid-19 mengalami pergeseran yang drastis ke arah dinamis setelah menghadapi berbagai tantangan yang berubah-ubah. Di samping itu pula, dalam perkembangannya pergeseran kepemimpinan madrasah setelah masa Covid-19 perlu mempertimbangkan lebih lanjut tiga corak kepemimpinan madrasah yang dikembangkan berikut, yaitu: kepemimpinan kolaboratif, fleksibel-adaptif, dan berkeadilan sosial.